Attitudes and behaviors towards vaccination in Portuguese nursing students - Marques-Vieira, Cristina Maria Alves (2023)
Knowing the attitudes and behaviors of nursing students in relation to vaccination is important because they will soon be determinant for the health literacy of the population. Vaccination remains the most effective response in the fight against communicable diseases, including COVID-19 and influenza. The objective of this study is to analyze the attitudes and behaviors of Portuguese nursing students with regard to vaccination. A cross-sectional study was carried out, with data collection from nursing students at a university in Lisbon, Portugal. A sample of 216 nursing students was obtained, representing 67.1% of the students enrolled in this university. What stands out from the results of the questionnaire “Attitudes and Behaviors in Relation to Vaccination among Students of Health Sciences” is that for the majority of students the answers were positive; in addition, 84.7% had a completed vaccination schedule for COVID-19. Being a nursing student, being in the final years of the course and being a woman are the factors that most influence the positive attitude of the students. The results obtained are motivating, because these students will be the future health professionals most likely to integrate health promotion programs through vaccination.